Peran Literasi Digital Dalam Pembelajaran Daring Selama Pandemi Covid-19 - Sunarmintyastuti Sunarmintyastuti; Hanggono Arie Prabowo; Loecita Sandiar; Aster Pujaning Ati; Subhan Harie; Lidya Natalia Sartono; Sigit Widiyarto (Jurnal Ilmiah Wahana Pendidikan, 2022)
Digital literacy was not just the ability to operate well, and only know the hardware and software, but more than that. Ability to control emotions, cognitive and social abilities. Online learning required digital literacy. So that students were able to learn well. The purpose of this study was to determine the role of digital literacy in online learning during the covid-19 pandemic. In addition to knowing the online learning process during the covid-19 pandemic, and to found out the obstacles during online learning at home. The research method used was a qualitative method. Data were taken by means of interviews and documentation. Respondents were 2 high school students and 3 junior high school students in Bogor Regency. The result of this study was that the lack of digital literacy in students could result in less than optimal online learning. The role of digital literacy in online learning is very dominant. One of the keys to successful online learning was digital literacy. Barriers that arose in online learning, were more dominant to external factors. Home learning required parental supervision to help with home learning